UJI AKTIVITAS DEODORANT SPRAY EKSTRAK ETANOL DAUN KITOLOD (Isotoma longiflora (L.) C. Presl) TERHADAP BAKTERI Staphylococcus aureus - Simorangkir, Delisma Marsauli; Purba, Gratia Apulia CP; Br Sembiring, Tio Ranti Sari; Laia, Sardamai Laia (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2026)
This study aims to determine the effectiveness of ethanol extract of cytolod leaves (Isotoma longiflora (L.) C. Presl) formulated in spray deodorant preparations as an antibacterial against Staphylococcus aureus. The extraction of cytolod leaves is carried out by the maceration method using 96% ethanol solvent. Spray deodorant preparations are made in three different extract concentrations, namely 3% (F1), 5% (F2), and 8% (F3), with positive control using commercial deodorant (AXE) and negative control in the form of a base preparation without extract. Antibacterial effectiveness testing was carried out using the suction diffusion method. The results of the physical evaluation showed that all formulas met the requirements of organoleptic, pH, clarity, viscosity, drying time, sprayability, and did not cause irritation to the skin. The results of the antibacterial activity test showed that the higher the concentration of the extract, the larger the barrier zone formed. Formulas with a concentration of 8% (F3) show the most effective inhibition activity with an average inhibition zone diameter of 15.73 mm, which belongs to the strong category.